Nutritional quality of Stenotaphrum secundatum and Brachiaria humidicola for goats - Simon P Ginting; Andi Tarigan (Jurnal Ilmu Ternak dan Veteriner, 2006)
The study was aimed to evaluate several nutritional quality parameters (chemical composition, intake and digestibility) in goats of S. secundatum and B. humidicola known to be highly and moderately shade tolerant species. The species of Pennisetum purpureuphoides was used as a control diet. These forages were offered to 21 male Kacang goats with an average body weight of 15.2 kg. The animals were divided into three groups based on the body weight, and were randomly allocated to one of the three forages species in a Completely Randomized Design. During the adaptation period (14 days) and the intake monitoring period (5 days) after the adaptation period the forages were offered ad lib. During the feces and urine collection period (7 days) feed was offered at 90% of the maximum  intake to minimize the intake fluctuation. The dry matter content of S. secundatum (332 g kg-1DM) and B. humidicola (321 g kg-1DM) were relatively higher than P. purpureuphoides (211 g kg-1DM), while the organic matter content were relatively equal among the three forages species. The crude protein content of S. secundatum (83 g kg-1DM) and B. humidicola (85 g kg-1DM) was almost identical, but were lower than that of P. purpureuphoides (111 83 g kg-1 DM) The NDF and ADF contents were relatively similar among the forage species. The dry matter (DM) intake of goats fed S. secundatum (588 g d-1) or fed B. humidicola (577 g d-1) did not differ (P>0.05), but it was higher (P>0.05) than dry matter  intake of goats fed P. purpreuuphoides. The similar trend was shown when DM intake was expressed in the percentage of body weight (3.60%, 3.55% and 2.77% BW, respectively) or when expressed as gram per kg BW0.75 which were 35.5, 35.6 and 27.7 g/kg BW0.75 respectively. The digestion coefficient of DM and OM were not different (P>0.05) between S.secundatum and B. humidicola, but it was higher than that in P. purpureuphoides. The digestion coefficient of energy were not different among these forages. The N balances were positive (3,0–3,6 g d-1) in goats offered these forages. It is concluded that the nutritional qualities of S. secundatum and B. humidicola were comparable, and it is relatively higher that the P. purpureuphoides when offered to goats as the sole feed. Key Words: Nutritional Quality, Grass Species, Goats